2021-2022 Greater Voyageurs Ecosystem wolf pack and population size report - Gable, Thomas D; Homkes, Austin T; Bump, Joseph K (2022)
This report presents and discusses data on wolf population metrics collected during 2021-2022 in the Greater Voyageur Ecosystem, Minnesota. In 2021-2022, we estimated the area of 9 wolf pack home ranges/territories, determined the size of 14 wolf packs, and obtained 7.3 independent observations of the same size for each pack. The survey effort in 2021-2022 was the same as 2020-2021 and represents the most intensive survey effort, in terms of number of packs and territories studied, to date in the Greater Voyageurs Ecosystem. We estimate that wolf population density in the Greater Voyageurs Ecosystem in 2021-2022 was 63.2 wolves/1000 km2 (95% confidence interval: 50.3-83.8 wolves/1000 km2). This density represents a 16% increase in population density from 2020-2021 and a 48% increase from the recent population low in 2019-2020 of 42.7 wolves/1000 km2. The increase in population density is largely attributable to increased pup survival, which likely increased pack size. We compared current wolf population density and population metrics to historical wolf density and population metrics in the Greater Voyageurs Ecosystem. This assessment suggests that wolf density in the GVE has changed little since the late 1980's, and that the GVE has sustained a high-density wolf population for decades.